Perselisihan mazhab nahu Basrah dan Kufah dan implikasinya terhadap pemahaman dan penterjemahan Quran - Ab. Halim Mohamad , (Penerbit Universiti Kebangsaan Malaysia, 2007)
Some of the differences in reading the verses of the Qur'an represent the differences among the Arabic grammar schools besides the differences in the Arabic dialects. Such differences can influence the meaning of Quranic verses. However, such differences do not involve the fundamental beliefs in Islam but those related to the legal and juristical domains according to the Muslims in the Sunnite schools of theology and jurisprudence. This article discusses some aspects of differences between the Arabic grammar schools of Basra and Kufah with reference to the same verses of the Quran for observation and analysis. Some differences between them lead to the different meanings in understanding and interpretation some verses of the Qur'an. In the context of the translation of the Quranic verses into the Malaysian and Indonesian languages, it discovers that their translations incline towards either the Basra grammar school or the Kufah one. This short exposure indicates that the activities of the translation of the Qur'an into the Malaysian and Indonesian languages could be done more accurately and comprehensively according to the reliable sources